Micro-albuminuria in non-diabetic acute ischaemic stroke: prevalence and its co-relation with stroke severity - Singh, Sumeet; Singh, Harpreet; Singh, Tarsem Pal (International Journal of Research in Medical Sciences, 2017)
Background: Microalbuminuria is not only a predictor of subsequent kidney disease, but also an indicator of generalised endothelial injury and a manifestation of endothelial dysfunction. The present study is aimed to determine the prevalence of microalbuminuria among non–diabetic ischaemic stroke patients and find its correlation with ischaemic stroke which eventually will aid us in coming up with potent strategies to provide better prevention and cure. Methods: The present study was conducted in Department of Medicine in collaboration with Department of Biochemistry and Department of Radiology, Guru Nanak Dev Hospital, Amritsar, Punjab, India after taking approval from institutional thesis and ethical committee. The study included 60 patients (30 Cases + 30 Controls) in age group 20-80 years diagnosed as stroke and haemorrhage ruled out by NCCT Brain/MRI Brain at admission. Cases were patients with history of hypertension with acute ischaemic stroke. Controls were age and sex matched patients with no history of hypertension with acute ischaemic stroke. The microalbuminuria was assayed by immunoturbimetry. The stroke severity was assessed by NIH Stroke Severity scale. P value less than 0.05 was considered the level of significance. Results: The overall prevalence of microalbuminuria in acute ischaemic stroke patients was 41.67%. When comparing NIH SS (National Institutes of Health Stroke Scale) score with the levels of albumin in urine, there was a significant positive correlation with urinary albumin levels and stroke severity in the patients having urinary albumin levels in microalbuminuria range both in Case group and Control group with P value less than 0.05. Conclusions: Urine albumin excretion had a positive correlation with the NIH SS Score of the patient in acute ischemic stroke. Those with a higher NIH SS Score had a higher rate of urine albumin excretion and vice versa. Therefore, measurement of microalbuminuria may help to assess those who are at increased risk of severe stroke and may require a more aggressive management.